Personal self-determination and dignity: A legislature of consolidation - Juan Carlos Carbonell Mateu (Cuadernos Electrónicos de Filosofía del Derecho, 2023)
Various legislative decisions are analyzed that express the recognition of the capacity for personal self-determination, an essential aspect of human dignity and the free development of personality. These include the regulation of euthanasia and assisted suicide, the guarantee of sexual freedom, abortion, and other issues such as transgender rights and prostitution. Cinematic references that address each of these issues are also included.